INNOVATING STUDENT ADMISSION USING NEUROSCIENCE PERSPECTIVE: LEARNING FROM MUHAMMADIYAH VOCATIONAL SCHOOLS - Mohammad Jailani; Djamaluddin Perawironegoro; Hendro Widodo (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2021)
The pandemic COVID-19 has opened new horizons in all parts of the world, including in education. Educational institutions must make breakthroughs related to the number of student admissions, which has decreased significantly, especially at Vocational School of Muhammadiyah 3 Yogyakarta. The purpose of this study was to find a promotion model for student admissions from a neuroscience perspective at Vocational School of Muhammadiyah 3 Yogyakarta. This study uses a qualitative method. The subjects of this study were the principal, the vice principal for student affairs, the vice principal for public relations, the head of the admission committee, and the prospective students. Researchers used observation, interviews, and documentation as data collection techniques. The data were analyzed using the Miles and Huberman model, namely data reduction, display data, and conclusion drawing/verification data. This study indicates that neuroscience as a brain approach (cortex prefrontal) can attract the sympathy of prospective new students to study at Vocational School of Muhammadiyah 3 Yogyakarta. It is a solution to meet the target group for majors at school. This research has implications for school management and Islamic education management in student admission department.